Model-assisted comparison of sugar accumulation patterns in ten fleshy fruits highlights differences between herbaceous and woody species. (25th April 2020) - Cakpo, Coffi Belmys; Vercambre, Gilles; Baldazzi, Valentina; Roch, Léa; Dai, Zhanwu; Valsesia, Pierre; Memah, Mohamed-Mahmoud; Colombié, Sophie; Moing, Annick; Gibon, Yves; Génard, Michel
Abstract: Background and Aims: Sugar concentration is a key determinant of fruit quality. Soluble sugars and starch concentrations in fruits vary greatly from one species to another. The aim of this study was to investigate similarities and differences in sugar accumulation strategies across ten contrasting fruit species using a modelling approach. Methods: We developed a coarse-grained model of primary metabolism based on the description of the main metabolic and hydraulic processes (synthesis of compounds other than sugar and starch, synthesis and hydrolysis of starch, and water dilution) involved in the accumulation of soluble sugars during fruit development. Key Results: Statistical analyses based on metabolic rates separated the species into six groups according to the rate of synthesis of compounds other than sugar and starch. Herbaceous species (cucumber, tomato, eggplant, pepper and strawberry) were characterized by a higher synthesis rate than woody species (apple, nectarine, clementine, grape and kiwifruit). Inspection of the dynamics of the processes involved in sugar accumulation revealed that net sugar importation, metabolism and dilution processes were remarkably synchronous in most herbaceous plants, whereas in kiwifruit, apple and nectarine, processes related to starch metabolism were temporally separated from other processes. Strawberry, clementine and grape showed a distinct dynamic compared with all other species. Conclusions: Overall, these results provide fresh insights into species-specific regulatory strategies and into the role of starch metabolism in the accumulation of soluble sugars in fleshy fruits. In particular, inter-specific differences in development period shape the co-ordination of metabolic processes and affect priorities for carbon allocation across species. The six metabolic groups identified by our analysis do not show a clear separation into climacteric and non-climacteric species, possibly suggesting that the metabolic processes related to sugar concentration are not greatly affected by ethylene-associated events.